Concurrent Training with Blood Flow Restriction does not Decrease Inflammatory Markers - de Souza, Thiago Mattos Frota; Libardi, Cleiton Augusto; Cavaglieri, Cláudia Regina; Gáspari, Arthur Fernandes; Brunelli, Diego Trevisan; de Souza, Giovana Vergínia; Ugrinowitsch, Carlos; Min Li, Li; Chacon-Mikahil, Mara Patricia Traina (International Journal of Sports Medicine, 2018)
The aging process is associated with several changes in the elderly such as the decrease in cardiorespiratory fitness, strength and muscle mass, in addition to chronic low-grade inflammation. Concurrent training with blood flow restriction can be an interesting alternative to improve functional capacity with low mechanical stress in the elderly. The purpose of this study was to compare the inflammatory effects in older individuals submitted to two different protocols of concurrent training. Twenty-two healthy older adults (63.7±3.8 years; 69.8±8.9 kg; 1.6±0.1 m) performed 12 weeks of concurrent training (CT) or concurrent training with blood flow restriction (CTBFR) and the effects on inflammatory markers were analyzed. We found inflammatory behavior for the CTBFR group with a significant difference in serum concentration of C-reactive protein between pre- and post-moment (0.96±0.37 to 1.71±1.45, p=0.049), with no difference between groups, and a time effect in interleukin-6 (pre=0.86±0.43; post=1.02±0.46, p=0.016). We conclude that the CTBFR showed a pro-inflammatory profile after the period of intervention whereas the CT showed the opposite.
Keywords: C-reactive protein; interleukin-6; interleukin-10; tumor necrosis factor-α; thigh blood pressure cuff